Botanical extracts as biofungicides against fungal pathogens of rice - Wong, Mui Yun; Hamid, Sathyapriya; Iskandar Shah, Nor Afifah; Ab Razak, Nurul Husna (Universiti Putra Malaysia Press, 2020)
Diseases such as blast, brown spot and sheath blight considerably affect the health and productivity of rice worldwide. Chemical fungicides have been routinely used in combating these diseases; however, a safe and environmental-friendly approach using bio-fungicides is desirable in disease management of food crop such as rice. Identification of botanical extracts with antifungal potentials would be instrumental in the development of biofungicides. In this study, the antifungal potentials of Andrographis paniculata, Backhousia citriodora, and Phaleria macrocarpa against selected rice fungal pathogens were analysed. Crude extracts obtained from leaves of these plants were diluted to 5, 10, 15, and 20% and tested against Pyricularia oryzae, Exserohilum rostratum, and Rhizoctonia solani in vitro using poisoned agar method. Percentage inhibition of diameter growth (PIDG) of each crude leaf extract against test pathogens was calculated. The aqueous extract of A. paniculata showed a significant mycelial inhibitory effect against P. oryzae at 20% concentration (PIDG 81.9%) as compared to other test concentrations and pathogens. On the contrary, the aqueous extract of B. citriodora at 15 and 20% concentrations had little influence on the mycelial growth inhibition on P. oryzae and E. rostratum with PIDG values less than 50%. In addition, P. macrocarpa methanol extracts at concentration of 10% and above significantly inhibited the mycelial growth of P. oryzae, E. rostratum, and R. solani (PIDG 100%). Phaleria macrocarpa leaf extract had been identified to give the highest efficacy against all three rice pathogens in vitro and therefore, has the potential to be developed into a biofungicide as a safe alternative to synthetic fungicides for disease management of rice.